PERILAKU MAHASISWA MASA PANDEMI PERSPEKTIF TEOLOGI ISLAM (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2022)
This study focuses on the behavior of students during the pandemic from the perspective of Islamic theology. The purpose of this study was to find out the academic behavior of students during the pandemic from the perspective of Islamic theology. Academic behavior can be interpreted as the tendency of a person's behavior when he learns academic things. Learning behavior can be interpreted as an activity that takes place in active interaction with the environment that results in changes, knowledge, understanding, and attitude values. This research is field research, using qualitative data types. Data sourced from primary and secondary data. Primary data is in the form of field findings in the form of interview observations with AFI students batch 2018 and observations in the field. Secondary data is in the form of literature and documents related to this research, both books, journals, theses and also through the internet. Data collection techniques using descriptive methods. The results showed that the academic behavior of the 2018 AFI students in terms of Islamic theology, including that their academic attitudes or behavior were partially inclined to the Mu'tazilah school, where students had the freedom to do and have academic desires. All academic actions carried out by students are purely based on the actions of the students themselves. Some other students, leaning towards the Jabariyah school, believe that students in all their academic actions are controlled by Allah. Students do not have freedom of academic behavior, which means that students do not have power over all academic behavior, they are controlled in all their actions and do not even have academic will and endeavors. And some others, leaning towards the Qodariyah school, are true to the name that students have power and freedom in all matters of academic behavior. Likewise, the academic behavior of other students, leaning towards the Asy-Ariyah school, is that God is the real maker of student behavior. Meanwhile, for the Khawarij, Murji'ah, Shi'a, and Maturidiyah schools, they were not found at all. Keywords: Academic behavior, students, Islamic Theology